2013
DOI: 10.1038/ncomms3364
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs confer phenotypic robustness to gene networks by suppressing biological noise

Abstract: miRNAs are small non-coding RNAs able to modulate target-gene expression. It has been postulated that miRNAs confer robustness to biological processes, but a clear experimental evidence is still missing. Using a synthetic biology approach, we demonstrate that microRNAs provide phenotypic robustness to transcriptional regulatory networks by buffering fluctuations in protein levels. Here we construct a network motif in mammalian cells exhibiting a “toggle - switch” phenotype in which two alternative protein expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 51 publications
(83 reference statements)
4
131
0
Order By: Relevance
“…In sum, here we found that post-transcriptional control of a master transcriptional regulator provides an efficient mechanism that assures canalized development and that stabilizes a transcriptional network during development and in adult animals. The role of post-transcriptional control in stabilizing the activities and levels of key activators of systems based on feedback loops has been previously proposed 46,47,51 , but to the best of our knowledge, our work constitutes the first theoretical and experimental example of this control principle.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In sum, here we found that post-transcriptional control of a master transcriptional regulator provides an efficient mechanism that assures canalized development and that stabilizes a transcriptional network during development and in adult animals. The role of post-transcriptional control in stabilizing the activities and levels of key activators of systems based on feedback loops has been previously proposed 46,47,51 , but to the best of our knowledge, our work constitutes the first theoretical and experimental example of this control principle.…”
Section: Discussionmentioning
confidence: 83%
“…It has been previously suggested that post-transcriptional control (for example, by miRNAs) could be used to diminish variability in biological systems [46][47][48][49][50][51] . In this context, we speculate that the high-transcriptional/high-turnover Clk profile stabilizes the circadian system by minimizing the consequences of transcriptional noise and/or by allowing rapid transcriptional feedback control.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, our work and several recent publications demonstrated that synthetic gene circuits offer a powerful tool, in a largely controlled manner, to understand the fundamental design principles of complex cellular systems (12,13,15). Although the synthetic circuit used in our study could not be fully isolated from the cellular environment because natural miR-21 targets may compete with the synthetic ceRNAs, our model deviation suggested that taking endogenous miR-21 targets into account rescales only the parameter θ in our computational model but does not change any of our conclusions (SI Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic biology provides a complementary approach to investigate miRNA-mediated regulations in a controlled and largely isolated biological setting by using engineered genetic circuits (11). Synthetic circuits have been constructed to help elucidate the underlying design principles of network motifs that combine transcriptional and miRNA-mediated regulations (12)(13)(14). It has also been demonstrated that miRNAs can generate a threshold in target gene expression by using a bidirectional reporter assay in mammalian cells (15).…”
mentioning
confidence: 99%
“…Multi-miRNA-multi-mRNA models have been formulated for specific modules where the targets regulate miRNA transcription, e.g., 2miRNA-2mRNA networks regulating the cell fate/differentiation decision (Lu et al 2013;Yan et al 2014), feedback loops with one miRNA and one target whose protein product regulates miRNA expression (Siciliano et al 2013), or modules where one of the targets is a TF that regulates expression of the other targets (Riba et al 2013). However, we limit our discussion to models where the target proteins have no effect on miRNA activity or concentration.…”
Section: Introductionmentioning
confidence: 99%